The Ability of Ferns to Accumulate Heavy Metals (Hg, Pb And Cd) In The Waters of The Gorontalo River - muhamad iksan; La Aba Aba; Kusrini Kusrini (Hasanuddin University, 2019)
Sustainable development can be caused by more human’s activity. This activity, it will have an impact on the surrounding environment which can disrupt the stability of the ecosystem, one of which is the river water ecosystem. The research aims to determine the ability of ferns in accumulating heavy metals so that they can be used as indicators of the depletion of river waters ecosystem environments and can be used as fitoremediant areas of waters which accumulate heavy metals. This research is descriptive quantitative. Retrieval of initial data or sample in this study used survey methods and random sampling techniques, testing samples by using the Ranger X-ray Flourenciece (XRF) method. Based on the results of the study that, ferns can accumulate heavy metals, the parts that accumulate are located below the root surface and above the soil surface, namely stems and leaves. In the roots have more amount in accumulating heavy metals than in the stem and leaves, this is because the metal is indicated on the soil. From these results, it can be concluded that ferns can be used as water purification plants in river ecosystems that are indicated by heavy metals.